Knowee
Questions
Features
Study Tools

Simplify the following expressions using Boolean algebra:a) (AB’C’ + AB’C + ABC + AB’C) (A + B)

Question

Simplify the following expressions using Boolean algebra:

a)

(ABC+ABC+ABC+ABC)(A+B)(AB' C' + AB' C + ABC + AB' C)(A + B)

🧐 Not the exact question you are looking for?Go ask a question

Solution

1. Break Down the Problem

We need to simplify the Boolean expression (ABC+ABC+ABC+ABC)(A+B)(AB'C' + AB'C + ABC + AB'C)(A + B).

2. Relevant Concepts

We will use Boolean algebra rules such as:

  • Idempotent Law: A+A=AA + A = A
  • Complement Law: A+A=1A + A' = 1
  • Distribution: A(B+C)=AB+ACA(B + C) = AB + AC
  • Absorption Law: A+AB=AA + AB = A

3. Analysis and Detail

Start by simplifying the inner expression:

  1. Simplify ABC+ABC+ABC+ABCAB'C' + AB'C + ABC + AB'C:

    • Combine ABCAB'C terms: ABC+ABC+ABC=ABC+ABC+ABC=AB(C+C)+ABCAB'C' + AB'C + ABC = AB'C' + AB'C + ABC = AB' (C' + C) + ABC
    • Using Complement Law C+C=1C' + C = 1: =AB(1)+ABC=AB+ABC= AB' (1) + ABC = AB' + ABC
  2. Now, our expression becomes: (AB+ABC)(A+B)(AB' + ABC)(A + B)

  3. Distribute A+BA + B: (AB+ABC)(A+B)=ABA+ABB+ABCA+AB(AB' + ABC)(A + B) = AB'A + AB'B + ABCA + AB

  4. Simplify each term:

    • ABA=AB(Idempotent Law)AB'A = AB' \quad (\text{Idempotent Law})
    • ABB=0(since BB=0)AB'B = 0\quad (\text{since } B'B = 0)
    • ABCA=ABC(Idempotent Law)ABCA = ABC \quad (\text{Idempotent Law})
    • AB=ABAB = AB

    So we have: AB+0+ABC+AB=AB+ABC+ABAB' + 0 + ABC + AB = AB' + ABC + AB

  5. Combine terms:

    • We can factor ABAB out: =AB+A(B+BC)= AB' + A(B + BC)
    • Using Absorption Law B+BC=B(1+C)=BB + BC = B(1 + C) = B: Thus, =AB+AB= AB' + AB

4. Verify and Summarize

  • The simplified expression combines AB+ABAB' + AB and using Absorption Law leads us to conclude this is simplified.

Final Answer

The simplified expression is: AB+AB AB' + AB

This problem has been solved

Similar Questions

2) What is the simplest Boolean expression equivalent to A’B’C + ABC’?A) A’CB) A’ + CC) A’C’D) AC

using boolean algebra simplify following (overline A + B)(A+C)

The Boolean expression x'y+yz+xz can be reduced toa.x'y+xzb.x'y+yz+xzc.x'y+yzd.yz+xz

Using Boolean laws simplify each of the following propositions:a. a ∧ b ∨ a ∧ ¬b

onstruct a truth table for the following boolean expressions of ABC + NOT A NOT B NOT C

1/2

Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.